pembelajaran berbasis proyek pada siswa efl dalam menulis esai - Amatul Firdausah; Dina Merris Maya Sari (Peneliti.net, 2020)
Essay writing with Project Based Learning on EFL students 'is considered as one of the most important academic courses in a supposed program help develop students' ability. The subjects of this study were 10 class 2019 A students of STKIP PGRI Sidoarjo English language education study program. The instrument used by the researcher was a questionnaire, observation checklist and a rubric score. The data analysis technique uses qualitative data. In analyzing essays writing data using 15 quistionnaires about the project-based application method (PBL) in writing essays using google form accompanied by the answer